Optimization of Processes and Technologies in Cargo Transportation - Abdirakhimov Azizbek Abdiqaxxor o’g’li (Genius Publishing Group, 2023)
Nowadays, a number of techniques and technologies have been used in the most optimal ways for fast, easy and high-quality transportation of cargo for some time. Nevertheless, in this article we will consider the issues of optimization of cargo transportation processes and technologies in modern logistics.
Keywords: Freight transportation; logistic operations; transportation processes; logistic systems